THE QUESTION OF THE USE OF BLUM TAXONOMY IN THE TEACHING OF KARAKALPAK PROSE WORKS (TAMADDUN NURI JURNALI, 2024)
The article presents scientific considerations on the importance of the author's application of Bloom’s taxonomy and its effectiveness in teaching prose works in literature lessons.